Organizational Learning and Private College Performance: The Role of Capabilities' Hierarchy - Ampauleng, Ampauleng; Salma Abdullah (International Ecsis Association, 2023)
This study proposes a model of the influence of organizational learning on the performance of private universities (PTS) in Makassar City. This study collected data through a survey approach to 294 leaders of PTS. The analysis tool uses WarpPLS 7.0. The results of this study found that organizational learning can encourage dynamic abilities. However, organizational learning is not significant to substantive abilities. Thus the study found a new concept. However, this study reveals that organizational learning can significantly drive dynamic abilities and encourage substantive capabilities. The study also found that dynamic ability can significantly drive substantive ability and PTS performance. Favorable substantive ability can drive PTS performance. Finally, dynamic capabilities significantly drive substantive and performance capabilities. Therefore, this study confirmed the validity of the DCV theory in the PTS environment.